Oil and gas exploration and production reserves, costs, contracts - Bret-Rouzaut, Nadine (Editions Technip, 2011)
Annotation The steps that lead to the production of oil and gas are diverse, complex, and costly. They are diverse because the detection of oil and gas involves input from many specialties, ranging from geology to reservoir engineering. They are complex, as shown by the development of the job of the petroleum architect, who coordinates all the operations. They are costly, as the investments for exploration and production represent more than half of all investments in the oil and gas sector. Moreover, exploration is a risky activity, both from the technical and financial viewpoint: only one well in five produces marketable oil. Meanwhile, the areas for exploration and production are spread throughout the world.
Translation of: Recherche et production du pétrole et du gaz : réserves, coûts, contrats / 2nd edition, N. Bret-Rouzaut, J.P. Favennec ... for the second edition.
Includes glossary and index.
Keywords: Petroleum industry and trade.; Petroleum -- Prospecting.; elektronické knihy; electronic books